Antioxidants in Sport: Exercise-Induced Oxidative Stress, Dietary Strategies, and Performance Outcomes – A Review - Korohod, Tamara; Pietrzak-Chmiel , Martyna; Ramaneckaite, Paulina; Binkiewicz, Agnieszka; Ślesik, Maciej (Quality in Sport, 2026)
Background. Exercise induces reactive oxygen species (ROS) production, triggering both adaptive signaling and potential oxidative damage in skeletal muscle. While moderate ROS generation promotes beneficial training adaptations including mitochondrial biogenesis and improved insulin sensitivity, excessive antioxidant supplementation may paradoxically blunt these adaptive responses. Aim. This narrative review examines current evidence on exercise-induced oxidative stress, the role of dietary antioxidants, and the efficacy of supplementation strategies in athletic populations. Material and methods. Systematic search of PubMed, PubMed Central, Scopus and Web of Science (January 2026) using keywords: "exercise", "oxidative stress", "antioxidants", "vitamins C and E", "polyphenols", "CoQ10", "melatonin", "athletes", "performance", "recovery". Priority given to randomized controlled trials, meta-analyses and mechanistic reviews. Results. Chronic high-dose vitamin C (≥1000 mg/day) and E (≥400 IU/day) supplementation blunts training-induced mitochondrial biogenesis and endogenous antioxidant enzyme upregulation without consistent performance benefits. In contrast, polyphenol-rich fruits and